Pemanfaatan Kulit Singkong (Manihot Utilissima) Sebagai Bahan Alternatif Pembuatan Cuka Dengan Penambahan Konsentrasi Acetobacter Aceti Yang Berbeda - RAHMAWATI, Rani; , Dra. Suparti, M.Si (2015)
Cassava is only used for part of the meat, while the discarded cassava peel or as animal feed. Skin is usually only used as cassava flour, cassava, and other processed. One effort to empower cassava peel make vinegar products. This study aims to determine the effect of different concentrations of Acetobacter aceti on the quality of cassava peel vinegar on levels of acetic acid, total sugar levels and levels of total dissolved solids. Parameters measured physical parameter ie the texture, aroma, and chemical parameters such as pH and the levels of acetic acid, reducing sugar levels and levels of dissolved solids. The method used in this research is completely randomized design (CRD) with one treatment factor is the addition of different concentrations Acetobacter aceti (R1 = 5%, R2 = 10%, R3 = 15%). Results of the study are in treatment R1, R2, and R3. The highest concentration of acetic acid at R2 is 2.58%. The highest total sugar content in R1 is 1.575% the highest levels of total dissolved solids in R3 is 5.985 mg / L. The conclusion from this study is the addition of different concentrations of Acetobacter aceti on quality cassava peel vinegar on levels of acetic acid, total sugar levels and levels of total dissolved solids.